An Unprecedented Vapor-Phase Sintering Activator for Highly Refractory Proton-Conducting Oxides - An, Hyegsoon; Seunghyeok Im; Kim, Jun seok; Kim, Byung Kook; Son, Ji-Won; Yoon, Kyung Joong; Kim, Hyoungchul; Yang, Sungeun; Kang, Hyung mook; Lee, Jong-Ho; Ji, Ho-Il (American Chemical Society, 2022)
Proton-conducting oxides provide opportunities to boost the electrochemical characteristics of various energy conversion devices owing to their high ionic conductivity. While these oxides alone require high-temperature sintering above 1600 °C to gain full density, surprisingly, their thin membrane on Nibased electrodes can be readily densified even below 1400 °C. However, the underlying mechanism is still unclear despite their widespread use, thereby hindering reliable fabrication of electrochemical devices. Here we reveal the mechanism by which an unprecedented type of sintering activator, vapor-phase BaNiOx, released from the transient phase in the electrode, is responsible for the accelerated sintering of refractory proton-conducting oxides. In contrast to conventional solid-phase sintering additives, the vapor-phase sintering activator is naturally supplied with an optimally small amount, which minimizes the residue but achieves sufficient enhancement of the sinterability, leading to negligible degradation of the electrical properties of the membrane. These findings establish a platform for fabrication of protonic ceramic electrochemical devices.